EFFECT OF UREA AND/OR CRUDE GLYCERIN TREATMENT ON THE NUTRIENT COMPOSITION AND IN VITRO TRUE DIGESTIBILITY OF DIFFERENT VARIETIES OF RICE STRAW - Bora Bölükbas; Muhammad Waqas; Ayse Gizem Bölükbas; Ismail Kaya; Mustafa Salman (Journal of Animal and Plant Sciences, 2024)
This study aimed to evaluate the nutrient composition and in vitro true digestibility of three rice straw (RS) varieties with varying stem lengths (Vasco (V): short-stemmed, Cammeo (C): medium-stemmed, and Efe (E): long-stemmed) treated with urea and/or crude glycerin. Each RS variety was ensiled in laboratory-scale mini-silos for 30 days using the following treatments: i) Control, ii) 5 % urea (U) treated RS, iii) 5 % crude glycerin (G) treated RS, and iv) 5% urea + 5% crude glycerin (UG) treatment RS. The Vasco variety of RS exhibited superior nutritional value compared to the Cameo and Efe varieties, with a greater (P<0.05) in vitro true digestibility of dry matter (IVTDDM  (V:46.11%, C:41.17% and E:43.94%) as well as lower (P≤0.001) NDF (V:66.38%, C:71.68%, and E:68.59%) and ADF (V:43.61%, C:50.64%, and E:49.1%) levels. Silage of all cultivars demonstrated comparable responses to the applied treatments. The crude protein (P<0.001) and IVTDDM (P<0.001) were greater in all treatment groups where urea was used alone or in combination with crude glycerin. All cultivars showed a reduction in NDF (P<0.001) and ADF (P<0.001) levels with the application of crude glycerin treatment alone, but no significant effect was observed on IVTDDM values. In the interaction effect, Efe×UG showed higher (P<0.001) in vitro true digestibility while for in vitro NDF digestibility, Efe×U interaction exhibited higher (P<0.001) digestibility compared to other interaction effects. The findings of the study suggest that adding urea or a combination of urea and glycerin to rice straw improved its nutritional content and digestibility. Treating rice straw with a combination of urea (5%) and glycerin (5%) could be a promising strategy to improve its nutritional value for livestock feed.
Keywords: crude glycerin; digestibility; rice straw; silage; treatment; urea